Uberização e Plataformização: a exploração disfarçada de empreendedorismo - Rocha, Fábio Armando (2024)
In the face of changes brought about by the so-called Industry 4.0 and the impetus of Information and Communication Technologies (ICTs), the world of work undergoes a complete metamorphosis. Intermittent jobs, linked to a platform connected to mobile devices, enable a "gig economy" where services are provided through companies that mediate between the service user and the provider. The worker, once an industrial laborer, becomes a digital-era service proletarian today. The lack of opportunities in the formal job market, with its corresponding rights and social protection, shifts thousands of workers toward gig work through a platform. These platforms extract maximum surplus value from workers, providing neither fair compensation nor any rights outlined in labor laws. The neoliberal discourse of financialized capital supporting technology companies that develop and manage these platforms aligns with the ideology of freedom, flexibility, and entrepreneurship. This causes opacity in the exploitation, dependency, and impoverishment of the platformized working class. This research aims to study the new dynamics and impacts that Platform Capitalism and Gig Economy cause in the labor market and the working class as a whole. It also presents experiences that counter this model, such as platform cooperativism. This qualitative research employs a critical literature review and shares experiences to contribute to the theoretical discussion.